Hubungan Pengetahuan Kanker Serviks Dengan Deteksi Dini Pemeriksaan IVA Pada Wanita Usia Subur Di Kelurahan Tawaang Barat Manado - Sri Atikah; Ria Angelina Jessica Rotinsulu; Endang Puji Ati; Atik Sunarmi (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Cervical cancer generally affects women aged between 15 and 49 years. Globally in 2020, there were 19.2 million new cancer cases which caused nearly 10 million deaths, according to data from WHO. The WHO cancer profile also recorded around 604,127 cases of cervical cancer worldwide, where this incidence was the second largest in Asia with a percentage of 58.2%, or around 351,720 individuals affected by the disease. In Indonesia, based on data from Global Burden Cancer (GLOBCAN) described in the Indonesia Cancer Care Community (ICCC) article, cervical cancer is in second place in terms of the highest number of sufferers after breast cancer in women, with around 32,469 cases (17.2%) and the death rate was around 18,279 people (8.8%). Objective. Knowing the Relationship between Cervical Cancer Knowledge and Early Detection of Visual Inspection of Acetic Acid (IVA) in Women of Childbearing Age in Tawaang Barat Subdistrict, Manado City in 2023 Research Method. This research uses quantitative research with analytical survey methods and a cross-sectional approach. The sample in this study was women of childbearing age aged 25-49 years. The sample was taken using Cluster random sampling, obtaining a sample of 135 respondents. Data analysis used Chi square. Results. For sufficient knowledge, 53 people (39.3%), 78 people (57.8%) did not carry out early detection. The results of Chi square analysis for the relationship between knowledge of cervical cancer and early detection of VIA examination are p value (0.000) ˂α (0.05).